2015
DOI: 10.1104/pp.15.00801
|View full text |Cite
|
Sign up to set email alerts
|

AtJAC1 Regulates Nuclear Accumulation of GRP7, Influencing RNA Processing of FLC Antisense Transcripts and Flowering Time in Arabidopsis

Abstract: Lectins selectively recognize sugars or glycans for defense in living cells, but less is known about their roles in the development process and the functional network with other factors. Here, we show that Arabidopsis (Arabidopsis thaliana) JACALIN-LECTIN LIKE1 (AtJAC1) functions in flowering time control. Loss of function of AtJAC1 leads to precocious flowering, whereas overexpression of AtJAC1 causes delayed flowering. AtJAC1 influences flowering through regulation of the key flowering repressor gene FLOWERI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 82 publications
(123 reference statements)
2
43
0
Order By: Relevance
“…The jacalin homolog AtJAC1 (AT3G16470) plays a role in controlling the flowering time of A. thaliana . AtJAC1 regulates the expression of the repressor gene flowering locus C through interaction with glycine‐rich RNA‐binding protein 7 and as such influences the flowering time (Xiao et al, 2015). The jacalin homolog–restricted tobacco etch potyvirus movement 1 (RTM1, AT1G05760) restricts the long‐distance movement of tobacco etch potyvirus in the phloem by acting together with the nonlectin proteins RTM2 and RTM3.…”
Section: Resultsmentioning
confidence: 99%
“…The jacalin homolog AtJAC1 (AT3G16470) plays a role in controlling the flowering time of A. thaliana . AtJAC1 regulates the expression of the repressor gene flowering locus C through interaction with glycine‐rich RNA‐binding protein 7 and as such influences the flowering time (Xiao et al, 2015). The jacalin homolog–restricted tobacco etch potyvirus movement 1 (RTM1, AT1G05760) restricts the long‐distance movement of tobacco etch potyvirus in the phloem by acting together with the nonlectin proteins RTM2 and RTM3.…”
Section: Resultsmentioning
confidence: 99%
“…A lectin receptor-like kinase (lectin RLK) in which the lectin domain is coupled with a serine/threonine kinase domain has been found to play a critical role in Arabidopsis pollen development (Wan et al, 2008). Jacalin-Lectin-like proteins are mainly involved in jasmonic acid-mediated defence responses (Xiang et al, 2011), but it was recently found that Arabidopsis JACALIN-LECTIN LIKE1 (AtJAC1) regulates flowering time (Xiao et al, 2015), as previously demonstrated for the wheat JACALIN-like lectin VER2 (Yong et al, 2003).…”
Section: Fem32 Overexpression Suppresses Male Fertility and Enhances mentioning
confidence: 86%
“…As a result, this proximal polyadenylation inhibits the transcription of FLC through triggering H3K4me2 demethylation in the FLC locus (Marquardt et al, 2014). A few 3â€Č-end processing factors containing RNA-recognition motifs, such as flowering control locus a (FCA) and FPA, glycine-rich rna-binding protein7 (GRP7), cleavage stimulation factor 64 (CstF64), CstF77, and nuclear speckle RNA binding protein a (NSRa), affect the splice site selection and polyadenylation site usage of COOLAIR transcripts, leading to an altered ratio of proximal-distal spliced variants (Liu et al, 2007;Streitner et al, 2008;Liu et al, 2010;Hornyik et al, 2010;Streitner et al, 2012;Xiao et al, 2015;Bazin et al, 2018). Loss-of-function mutations in these factors decrease or increase the usage of COOLAIR proximal polyadenylation site, leading to upregulated or downregulated FLC transcription.…”
Section: As Of Flc Antisense Transcripts Regulates Flc Expressionmentioning
confidence: 99%
“…Two classes of COOLAIR transcripts bind to FCA and recruit PRC2 complex to FLC locus (Tian et al, 2019). The class I variants with proximal polyadenylation and the proximal-distal ratio of COOLAIR transcripts effect the histone methylation of H3K4me2, H3K36me3 and H3K27me3 (Marquardt et al, 2014;Berry and Dean, 2015;Xiao et al, 2015;Rosa et al, 2016). The class II COOLAIR transcripts with distal polyadenylation influence the degree of capping of the FLC nascent transcripts (Li et al, 2015).…”
Section: As Of Flc Antisense Transcripts Regulates Flc Expressionmentioning
confidence: 99%